Intravascular leiomyomatosis associated with uterine STUMP extending into the right atrium: a rare case report - Badusha, Asmin Shaikha; Mohandas, Mithun; Moni, Sheela; P. Kutty, Sathiamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Intravascular leiomyomatosis (IVL) is a rare benign smooth muscle tumor that originates from the uterus and proliferates within venous channels, occasionally extending into the heart. Smooth muscle tumour of uncertain malignant potential (STUMP) represents a borderline uterine neoplasm with unpredictable biological behavior. The coexistence of IVL and STUMP is exceptionally rare, posing diagnostic and therapeutic challenges. We report the case of a 52-year-old perimenopausal woman who presented with abdominal distension and bilateral lower limb pain for six months. Imaging revealed a large uterine mass with a thrombus extending from the pelvic and gonadal veins into the inferior vena cava (IVC) and right atrium. The patient underwent staging exploratory laparotomy with total abdominal hysterectomy, bilateral salpingo-oophorectomy, pelvic tumour excision, venotomy with thrombus extraction, and lymphadenectomy. Histopathology confirmed a spindle cell neoplasm consistent with a STUMP associated with intravascular leiomyomatosis. This case highlights the rare coexistence of STUMP and IVL with intracardiac extension. Comprehensive preoperative imaging, multidisciplinary surgical planning, and complete tumor resection are crucial to prevent recurrence and ensure favorable outcomes.